Sistem Informasi Koran DPRD Kalimantan Timur Berbasis Web - Hery Kurniawan; Arbansyah (Journal Of Informatics And Busisnes, 2023)
Research aims to develop a web-based Newspaper Information System for the Regional People's Representative Council (DPRD) of East Kalimantan using PHP and MySQL. The system is designed to expedite the distribution of information to DPRD employees, enabling them to access the newspaper quickly and efficiently. The use of PHP as the programming language and MySQL as the database management system is intended to create a stable, secure, and easily accessible platform. The system development methodology involves needs analysis, system design, implementation, and testing. Key functionalities of the system include news search and categorization, real-time access, and user interaction convenience. With the implementation of this web-based Newspaper Information System, it is anticipated to enhance operational efficiency, transparency, and information accessibility within the environment of the DPRD of East Kalimantan. Preliminary evaluation results indicate that the system has the potential to provide significant benefits in supporting information needs within the DPRD.